(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The training in preparing financial reports for the management of BUMDes Raharja and UKM players in Rancaekek Wetan Village, Rancaekek District, Bandung Regency aims to improve their ability to record and manage finances through the preparation of financial reports. BUMDes administrators and UKM players do not understand a good way of recording, especially those related to accounting.To realize these goals, support from academics is needed to get training in preparing BUMDes and UKM financial reports. The method used in this community service is training and assistance in preparing BUMDes and UKM financial reports through webinars and discussions related to BUMDes financial management issues and UKM players. The method of collecting data on this service activity is through observation and interviews with BUMDes administrators and one of the UKM players. The number of Participants who took part in the training was 15 people who were administrators of BUMDes and UKM players engaged in the trade of traditional Rengginang, Opak and Kolontong and services.The results of this training activity can be declared successful, seen from the enthusiasm of BUMDes administrators and UKM players during the training process and assistance in preparing financial reports.